COMPARATIVE ANALYSIS OF AFFECTIVE RESPONSE AND SUBJECTIVE PERCEPTION OF EFFORT IN SMALL SIDED GAMES WITH DIFFERENT DIMENSIONS - Marques, Julia Castellano (2019)
The objective of the study was to comparatively analyze the affective response and the subjective perception of effort (SPE) of soccer players of the category sub 15 in small-sided games in large (36x27m) and small (27x18m) field. The sample consisted of 31 male subjects with a mean age of 14.7±0.24. Everybody practiced soccer training regularly for more than six months in a club of the 1st division of the city of Rio de Janeiro. The data were collected through a research where the pleasure/displeasure scale of Hardy and Rejeski and the Borg scale for SPE were used. According to the results, players have more pleasure in playing small games in the smaller field. The SPE was bigger in the large field, and it was concluded that the games in the smaller field were more pleasant and less tiring, and may be a strategy to enhance the training in this category.